SPORT JOURNALISM AND PROFESSIONAL ETHICS: IDENTITY PROBLEM - Bojan Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
This subject represent part of larger research, research of influence of sport journalism on sports and social public. Therefore, in this shorter interpretation of this analysis, it will be expose just basic parts of research. This subject, especialy, pointing on some problems of professional ethics of sport journalists and effect of their identity, as inside of journalists proffesion as in public. Conclusion is that, those problems can be solved with creating of critical attitude toward negative phenomenon in sport.